(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Education is a formative process of every subject in a society, it is a right recognized in a tangible way. In the school environment, it infers a comprehensive process for all the actors of the student community. One aspect that has developed over time and that has had greater employability since the COVID-19 pandemic was resilience as a means of management and prompt attention to the process of adaptation and impact in the educational field. This document describes, based on legal criteria, the importance of the resilient process, also approached from the conceptual construction framework of various actors, considering educational resilience as an agent of transformative change in academic performance, as well as the importance of continuous training in and for all the actors of the educational community.